Understanding traditional acupuncture a practical handbook for health practitioners in the Philippines - Pantig, Alphonse Vergara (Acupuncture Therapeutic and Research Center and Socio-Pastoral Institute, 1996)
This book is intended to teach Filipinos traditional acupuncture within the context of primary health care in the Philippines. It uses the Chinese medical matrix. It also contains the theories of Yin and Yang and the five stages of change, the outline of the body in traditional Chinese medicine (TCM), basics of TCM physiology and pathophysiology and the four TM (traditional medicine) of diagnosis.